Analysis of Science Literacy Abilities Through Authentic Assessment of High School Students - Putri, Sri Rahayu; Hasruddin (Bioilmi: Jurnal Pendidikan, 2025)
Indonesian students' scientific literacy skills from 2000 to 2022 remain low, as their scores are below the average PISA (Philosophy of Science and Technology) completion score. This study aims to analyze high school students' scientific literacy skills in the field of biological technology innovation through authentic assessment. This research is descriptive and quantitative. The study was conducted at SMAN 1 Medan. The population was all 432 tenth-grade students from 12 classes. The sample size was 72 students from two classes: class X1 and class X5. Simple random sampling was used as the sampling technique. Data collection used authentic assessment instruments, consisting of 10 essay questions and a 25-item questionnaire. The data were analyzed using a descriptive percentage formula. The results showed that students' scientific literacy skills were in the adequate category, with a percentage of 57%. A score of 57% reflects that most students have a basic understanding of scientific concepts, but are unable to fully master them or apply them optimally in real-life contexts. Internal factors influencing students' scientific literacy skills are categorized as good, with a percentage of 73%, and external factors are categorized as good, with a percentage of 75%. The research results show that students' scientific literacy skills are generally in the "adequate" category, although influencing factors, such as the availability of facilities and infrastructure, the quality of learning, and the role of teachers, are classified as "good." This indicates an imbalance between the potential of a supportive learning environment and suboptimal student learning outcomes.